2019
DOI: 10.1002/ppp3.10057
|View full text |Cite
|
Sign up to set email alerts
|

From treetops to tabletops: a preliminary investigation of how plants are represented in popular modern board games

Abstract: Societal Impact Statement Plants have been elements in games throughout history. In an era where “digital pushback” is becoming more common, the impressions that representations of plants in board games have on an audience is not to be overlooked. By acknowledging the importance, beauty and history of the botanic world and its considerable impact on the daily lives of human beings connected to it, modern board games may offer an entertainment route towards awareness as well as an educational resource to challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The changing face of human interaction with plants and the natural environment is reflected in the applied arts, as exemplified by trends in motion picture animation (Ebedes, 2018;Prévot-Julliard et al, 2015;Lima, 2016). Moreover games and role-playing have growing potential to capture student and public interest in plant life (for example Borsos, 2019;Friedersdorff et al, 2019;Van Nuland et al, 2019).…”
Section: Transdisciplinary Approaches Addressing Plant Blindnessmentioning
confidence: 99%
“…The changing face of human interaction with plants and the natural environment is reflected in the applied arts, as exemplified by trends in motion picture animation (Ebedes, 2018;Prévot-Julliard et al, 2015;Lima, 2016). Moreover games and role-playing have growing potential to capture student and public interest in plant life (for example Borsos, 2019;Friedersdorff et al, 2019;Van Nuland et al, 2019).…”
Section: Transdisciplinary Approaches Addressing Plant Blindnessmentioning
confidence: 99%
“…2. Studies have found that students' species (including plants) literacy, attitudes, and identification skills improved after specific activities aimed at increasing their interest in local flora (Nyberg & Sanders, 2014;Kaasinen, 2019); workshops (Nates et al , 2012), outdoor educational programs (Fančovičová & Prokop, 2011;Wyner & Doherty, 2021), use of living organisms in the classroom (Krosnick et al, 2018;Krell & Schmidt, 2020) , visits to botanical gardens (Kissi & Dreesmann, 2017), or board games (Friedersdorff et al, 2019) and mobile applications (Hartman et al, 2019), were some of the proposals investigated.…”
Section: Educational Implications: Proposals To Counteract Plant Awar...mentioning
confidence: 99%
“…En cuanto a los dominios de conocimiento, al Aprendizaje Basado en Juegos ha sido explorado en campos tan diversos como son los idiomas (Wu et al, 2014), las matemáticas (Ramani et al, 2012), o la ecología (Friedersdorff et al, 2019); de entre todos estos campos destacan las temáticas vinculadas al pasado, que son muy populares tanto en número de juegos y jugadores como en estudios sobre dicho aprendizaje (Beavers, Sian M, 2020;Metzger & Paxton, 2016;Mozelius et al, 2017;Mugueta Moreno et al, 2022;Mz & Sy, 2008) aunque de nuevo la mayoría de trabajos se centran en el uso de videojuegos en entornos de educación formal.…”
Section: El Juego De Mesa Como Recurso De Aprendizaje Informalunclassified